Adoption intention and usage behavior of mHealth services in Bangladesh and China: A cross-country analysis. Issue 1 (16th December 2019) - Alam, Mohammad Zahedul; Hu, Wang; Hoque, Md Rakibul; Kaium, Md Abdul
Abstract : Purpose: The purpose of this paper was to explore the comparative influential factors affecting the behavioral intention and actual usage of mHealth services in two distinct national environments, i.e. China and Bangladesh, in relation to the international expansion of mHealth services. Design/methodology/approach: In this study, widely accepted Unified Theory of Acceptance and Use of Technology (UTAUT) with two additional variables, i.e. Perceived Reliability and Price Value have been selected as a theoretical framework. Primary data were collected from existing mHealth users among generation Y in both China and Bangladesh. A total of 296 and 250 questionnaires were deemed as usable for data analysis for Bangladesh and China, respectively. Findings: Performance expectancy and social influence had significant impact on the adoption intention of mHealth services for both countries. Effort expectancy and price value were insignificant factors for Bangladesh, whereas facilitating condition and perceived reliability were insignificant for China. Practical implications: The insights from this study could benefit mHealth services providers and those policymakers who seek to enter the Chinese and the Bangladeshi healthcare market. The dimensions identified in the study are based on a full assessment of mHealth usages experiences. Global service providers can use the dimensions identified by the paper to better assess their service performance on an international level. Originality/value: The paper is unique in that it is one of the first cross-country examinations of influential factors affecting the adoption of mHealth services in two different countries. This study confirms the applicability of extended UTAUT model in the context of mHealth services among the generation Y in developing countries such as China and Bangladesh.